The Influence of Pro-Inflammatory Factors on Sclerostin and Dickkopf-1 Production in Human Dental Pulp Cells Under Hypoxic Conditions - Janjić, Klara; Samiei, Mohammad; Moritz, Andreas; Agis, Hermann (Frontiers in Bioengineering and Biotechnology, 2019)
Sclerostin (Sost) and dickkopf (Dkk)-1 are inhibitors of the Wnt signalling pathway that plays a role in regenerative processes. Hypoxia-based strategies are used for regenerative approaches, but the influence of hypoxia on Sost and Dkk-1 production in a pro-inflammatory environment is unclear. The aim of this study was to assess if a pro-inflammatory has a different influence on Sost and Dkk-1 production in dental pulp cells (DPC) under normoxia than under hypoxia. Human DPC were treated with interleukin (IL)-1β, tumor necrosis factor (TNF)α or transforming growth factor (TGF)β, with L-mimosine (L-MIM) or hypoxia or a combination. Sost and Dkk-1 mRNA levels were measured with qPCR. TNFα, TGFβ, L-MIM or combined treatment do not modulate Sost and Dkk-1. IL-1β downregulates Sost. Hypoxia alone and together with inflammatory markers downregulates Dkk-1. In conclusion, there is a differential effect of hypoxia and IL-1 β on the production of Dkk-1 and Sost.